Effect of Organic Solvents on the Molten Globule State of Procerain: β-Sheet to α-Helix Switchover in Presence of Trifluoroethanol - Dubey, Vikash K.; Shah, Ashu; Jagannadham, Medicherla V.; Kayastha, Arvind M. (Protein and Peptide Letters, 2006)
The effect of methanol and trifluoroethanol (TFE) on the structure and folding of molten globule state of procerain, a cysteine protease from Calotropis procera, was studied by circular dichroism spectroscopy. The magnitude of ellipticity at 215 nm, as a measure of β-sheet content, is dependent on the concentration of the TFE. Interestingly, a switch over from the β-sheet structure of the molten globule state to α-helix was observed at 60% TFE and the ellipticity at 222 nm increased as a function of TFE concentration beyond this critical TFE concentration. Temperature induced unfolding of the molten globule state of procerain in 10% methanol showed stabilization of α-rich domain with concomitant destabilization of β-rich domain. Using higher concentration of methanol (20-40 %) had no stabilizing effect on the α-rich domain however, the β-rich domain was destabilized, indicating that the stability of the domains were not interdependent and that a low concentration of methanol induced stabilization in α-rich domain.
Keywords: Plant cysteine protease